PubMed: an untapped source for open educational resource images. - Svoboda, Ellie; Connolly, Teresa (Journal of the Medical Library Association, 2026)
Background: Open Educational Resources (OER) are free learning materials that benefit students in higher education, including in the health sciences. As more health sciences OER materials are created, there is a need for openly licensed health sciences images. Traditional OER repositories lack specialized health sciences imagery while PubMed is a biomedical database that has potential to fill this gap. Case Presentation: A nursing faculty partnered with a health sciences librarian to search PubMed for openly licensed images for a pathophysiology OER textbook. The librarian used existing filters in PubMed to identify articles that have Creative Commons licenses as well as images. The nursing faculty assessed these images and added relevant ones to the pathophysiology textbook. Conclusions: PubMed is a free resource that health sciences librarians use on a regular basis. Utilizing the database to find openly licensed materials allows librarians to use a familiar tool for a new and exciting purpose.